Bridge jobs in Europe - Giorgio Brunello; Monica Langella (IZA Journal of Labor Policy, 2013)
We study the transitions from career to gradual and permanent retirement by a sample of (Continental) European males aged 55 to 70 in the late 2000s. We find that only 14.6% of the workers in this sample moved from a career to a bridge job by the time of the interview, much less than in the United States, where this share is estimated at close to 60%. We use the cross country and time variation in employment protection legislation and minimum retirement age to study whether recent changes in these labour market institutions have had any effect on the transitions out of career jobs. We find that policies that have increased minimum retirement age and reduced the strictness of employment protection legislation have raised the hazard into gradual retirement in Northern and Central European countries and the permanence in career jobs in Mediterranean countries.
Keywords: J26; J11; J21; 330; Retirement; Europe; Bridge jobs; Pension reforms